Crear una colección de prendas maximalistas inclusivas como un nuevo modelo de negocio en la empresa CHARL’S BORDADOS - Pérez Rodríguez, Evelyn Xiomara (2024)
The research project focuses on introducing a new business model to Charl's Embroidery company that will enable the launch of a cutting-edge collection of inclusive maximalist garments for the LGBTIQ+ community, while also targeting new customers who identify with our products. The primary objective is to design a collection of inclusive maximalist garments as a new business model for Charl’s Embroidery, drawing inspiration from successful business models of other companies. The proposal aims to merge the art of embroidery and prints with a unique maximalist trend that has an inclusive focus. It is expected that this initiative will not only expand the diversity of the product catalog but also transform Charl's Embroidery's business model, positioning it as a leader in inclusive and creative fashion. The interview conducted with 20 members of the community, a design professional, and the manager allowed for the identification of the top five criteria to understand their tastes, preferences, and purchasing power. It is understood that the research has a qualitative approach as it allows for a precise understanding of the main characteristics to effectively determine the product to be offered to the LGBTIQ+ population. It is worth noting that the market is open to all individuals who wish to purchase products from this new inclusive business line. This project will address aspects such as market research, implementation methodology, and necessary technologies to carry out this innovative proposal